PENGARUH MANAJEMEN MODAL KERJA TERHADAP LIKUIDITAS DENGAN PROFITABILITAS SEBAGAI PEMODERASI PADA PERUSAHAAN MANUFAKTUR - Supramono Supramono; Cindy Christine Nanna (Bina Ekonomi, 2022)
This study aims to determine the effect of working capital management on liquidity with profitability as a moderation variable in manufacturing companies. The number of samples used was 41 companies obtained using the purposive sampling method. The source of the research data used is secondary data in the form of annual financial reports published by the official website of www.idnfinancials.com for the period 2016-2019. The data analysis techniques used are panel data analysis and Moderated Regression Analysis (MRA). The results of the study showed that working capital management does not have a significant effect on liquidity, profitability as a moderation variable is not able to moderate working capital management to liquidity.